Analisis Yuridis Temuan Insidental dalam Praktik Penyadapan Komisi Pemberantasan Korupsi - Ade Rachmad Hidayat; Arne Huzaimah; K.A. Bukhori (CV. Ulil Albab Corp, 2026)
This study examines the normative construction of the Indonesian Corruption Eradication Commission's (KPK) wiretapping authority, specifically concerning